What is 100th term of the following sequence?
1 , 2 , 7 , 1 6 , 2 9 , . . .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
We note that the first few differences between consecutive terms of the sequence are 1 , 5 , 9 , 1 3 , ⋯ . Let the terms be a n , then for n ≥ 1 we have:
a n + 1 − a n k = 1 ∑ n ( a k + 1 − a k ) a n + 1 − a 1 a n − 1 ⟹ a n ⟹ a 1 0 0 = 4 ( n − 1 ) + 1 = 4 n − 3 = 4 k = 1 ∑ n − k = 1 ∑ n 3 = 2 n ( n + 1 ) − 3 n = 2 ( n − 1 ) n − 3 ( n − 1 ) = 2 n 2 − 5 n + 4 = 2 ( 1 0 0 2 ) − 5 ( 1 0 0 ) + 4 = 1 9 5 0 4 Replace n + 1 with n .
Here, difference between 2 and 1 = 1 Difference between 7 and 2 = 5 = 1+4×1 And between 16 and 7 = 9 = 1+4×2 And between 29 and 16 = 13 = 1+4×3 And so... However, I won't tell the ultimate formula. But, for the above sequence, the equation = 2n²–5n+4 Now, for 100th term = 2×100²–5×100+4 =19504
Problem Loading...
Note Loading...
Set Loading...
The first differences are 1 , 5 , 9 , 1 3 .
The second differences are 4 , 4 , 4 , 4 .
Since second differences are same, the function is quadratic.
Since f ( x ) = x for 1 , 2 .
f ( x ) = k ( x − 1 ) ( x − 2 ) + x
Putting value of f ( 3 ) , k = 2 .
Now, f ( 1 0 0 ) = 2 ( 9 9 ) ( 9 8 ) + 1 0 0 = 1 9 5 0 4